[Dean of Architecture George Hasslein and Dean of Library Services David Walch] (1981)
On back: 'Architecture and Lib. dean David Walch', George Hasslein on left, David Walch on right. They are looking at records from the Julia Morgan Papers in Special Collections, which were donated in 1980.